Person Organizationfit dan Job Embededdness Sebagai Faktor Penentu Turnover Intention Pada Bank Mandiri Cabang Surabaya (STIE Rajawali Purworejo, 2025)
The unit of analysis in this study was PT Bank Mandiri Surabaya Branch, involving 50 employee respondents. The purpose of this study was to analyze and determine the effect of person-organization fit and job embeddedness on turnover intention. This study falls into the category of causal associative research, which aims to analyze the relationship between variables and how one variable influences another. Data analysis included descriptive analysis, research instrument testing (validity and reliability testing), multiple linear regression analysis, classical assumption testing, and hypothesis testing. The results of this study indicate that person-organization fit and job embeddedness simultaneously influence turnover intention. This is evidenced by a significance value smaller than the probability value with 0.000 <0.05. Person-organization fit has a significant negative effect on turnover intention. This is indicated by a significance value smaller than the probability value with 0.000 <0.05. Job embeddedness has a significant negative effect on turnover intention. This is indicated by a significance value smaller than the probability value with 0.000 <0.05.